In vitro digestibility and degradability of diets with sacha inchi cake in ruminants - Henao Zambrano, Juan Carlos (2020)
The aim of this work was to characterize chemically and nutritionally the cake generated from the extraction of oil from the sacha inchi seed, and to evaluate the in vitro digestibility and degradability parameters of ruminant diets with different inclusion levels. The determination of the dry matter (DM), crude protein (CP), ether extract (EE), fibre in neutral detergent (NDF) and fibre in acid detergent (FDA) of the sacha inchi cake was conducted. Four diets based on corn silage, corn grain, glycerol, soybean cake and sacha inchi cake were evaluated as protein substituents for soybean cake, in four proportions (0, 5, 10 and 15%). An amino acid profile and the digestibility and degradation kinetics of DM were performed. For the degradability study, samples were taken at 0, 3, 6, 12, 24, 48 and 96 hours to determine the disappearance of DM. The cake showed a concentration of 40.8% CP. The lysine and threonine values were 2.28 and 1.89 g/100 g sample, respectively. The in vitro digestibility of the diets did not show significant differences between them. The ruminal degradation kinetics of the diets was similar except at 0 and 96 h, showing a slight decrease between 0 and 6 h, to later increase in all diets. The results indicate that sacha inchi cake is a good feed alternative in ruminants and represents an important option as a substitute for soybean cake as a protein source.